2021
DOI: 10.2478/hukin-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Perceived Movement Quality and the Kinematic Pattern of Complex Skills in Gymnastics

Abstract: The study aimed to investigate the relationship between the perceived movement quality of a gymnastics skill and its kinematic pattern, as well as the influence of expertise. Thirty participants with different levels of gymnastics expertise (n = 10 visual experts, n = 10 motor experts and n = 10 novices) were recruited for the study. They were instructed to compare the movement quality of eleven video sequences, showing different handstand - back handspring performances. To extract the kinematics, the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…While constructing the regression equation the significance levels (p value -Beam walk test -.000, Shuttle run on Floor Exercise -.000, Over grip hang on Horizontal bar -.001, Flexed arm hang on Horizontal Bar -.013) are smaller than 0.05., all four regression coefficients are significant. As a result, it is possible to conclude that the variables Beam walk test, Shuttle run on Floor Exercise [15][16][17], Over grip hang on Horizontal bar, Flexed arm hang on Horizontal Bar have a substantial role in explaining variances in Gymnastics Performance [18][19][20][21]. The four variables selected in the regression equation explains 41 % of the total variability which is quite good and valid for estimating the Gymnastics Performance but according to this study it is appeared that these 07 variables does not affect the total performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While constructing the regression equation the significance levels (p value -Beam walk test -.000, Shuttle run on Floor Exercise -.000, Over grip hang on Horizontal bar -.001, Flexed arm hang on Horizontal Bar -.013) are smaller than 0.05., all four regression coefficients are significant. As a result, it is possible to conclude that the variables Beam walk test, Shuttle run on Floor Exercise [15][16][17], Over grip hang on Horizontal bar, Flexed arm hang on Horizontal Bar have a substantial role in explaining variances in Gymnastics Performance [18][19][20][21]. The four variables selected in the regression equation explains 41 % of the total variability which is quite good and valid for estimating the Gymnastics Performance but according to this study it is appeared that these 07 variables does not affect the total performance.…”
Section: Discussionmentioning
confidence: 99%
“…In the following studies, comparable occurrences were seen in the current study: Strength (static strength, speed strength, and endurance strength) and flexibility appear to be crucial for excellent performance, according to [6,9] Whereas in other study it was shown that 249 gymnasts participated in the Olympic opportunity programme for talent assessment, with the investigator identifying Strength, Speed, and Flexibility factors in his results. [5,19,21] Power velocity, isometric and explosive ability, strength endurance, and dynamic and static flexibility, on the other hand, are the most essential physical fitness parameters of the talent selection process in young male artistic gymnasts [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…Athlete's aerial tossing and turning attitude control The human body's air tossing, tilting, and turning movements are movements around the above three coordinate axes. 3 The direction cosine matrix of the outer azimuth angle under the rotational motion with attitude angles φ, θ and ψ is expressed as follows…”
Section: Methods Research Objectsmentioning
confidence: 99%
“…Furthermore, different specialists (motor specialists/visual specialists/novices) have different kinematic characteristics. However, the visual specialist group includes referees and coaches [22]. Thus, these previous studies suggested that the accuracy of technical evaluation and the cues considered necessary during evaluation differ depending on the internal factors of the evaluators.…”
Section: Eye Movements Of Sports Judges Research In Sports Psychologymentioning
confidence: 99%